Peran Fasilitator Pendamping Dalam Pengembangan Usaha Mikro Kecil Menengah (UMKM) Nasabah BTPN Syariah Di Kecamatan Wongsorejo Banyuwangi Jawa Timur - Latifah Ika Sari; Nisa Hafi Idhoh Fitriana (Jurnal Informasi Pengabdian Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) are an alternative that can restore and improve the national economy. In Wongsorejo, most of the women and mothers of BTPN Syariah customers are underprivileged business people who are struggling to obtain prosperity for their families. Realizing this, PT Bank BTPN Syariah is holding a MSME mentoring program by empowering women and mothers of its customers in all rural areas of Indonesia to be empowered to help improve the welfare of their families through the Bestee Program. The main aim of this mentoring activity is to convey good intentions to help others improve the prosperity of Micro, Small and Medium Enterprises (MSMEs). Mentoring activities through the BTPN Syariah Bestee program are carried out in several stages, namely location survey, introduction and assessment, discovery of obstacles, delivery of material, practice, as well as evaluation as the closing activity for one session. The results obtained from mentoring activities have a positive impact on all parties involved, especially BTPN Syariah mentoring customers who take part in the Bestee program.